Top Hats - Larry Bowne (Oz, 2007)
The photographs on the following pages were taken by students enrolled in the seminar "Some Manhattan Apartments," which I taught in the spring of 2007 in the Department of Architecture at Kansas State University in Manhattan, Kansas. The course investigated a local building type, the half-roofed, walk-up triplex apartment building.